Luminescent brightening floor containing inorganic polymer silicon resin
By using a multi-layer structure design containing inorganic polymer silicone resin in the floor material, combined with modified carbon nanotubes and modified polypropylene fibers, the shortcomings of traditional floor materials in terms of aesthetics, wear resistance, durability and luminous brightening characteristics are solved, and the wear resistance, stain resistance, crack resistance and luminous brightening effect of the floor are improved.
Patent Information
- Application Number
- CN202510077297.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-05-16
AI Technical Summary
Existing floor materials have shortcomings in aesthetics, wear resistance, durability and luminous brightness, especially when used for a long time, they are prone to cracks and wear, and lack sufficient brightness to be used in night or inadequate light environments.
A multi-layer structural floor design containing inorganic polymer silicone is designed, including a plain earth compaction layer, a colored concrete layer, a colored aggregate polymer surface layer, a graphic acid coloring layer and an elastic resin protective layer. Through the use of modified carbon nanotubes and modified polypropylene fibers, the wear resistance, crack resistance and luminous brightening effect of the floor are improved.
It has achieved improvements in the wear resistance, anti-fouling and crack resistance of the floor, and has luminous and brightening and decorative effects, which can reduce walking noise and heat island effect, and is suitable for a variety of application scenarios.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building construction, and in particular relates to a luminous brightening floor containing inorganic polymer silicone resin. Background Art
[0002] In modern construction and road engineering, the performance requirements for floor materials are getting higher and higher, especially in terms of aesthetics, durability and functionality. The floor must not only have excellent decorative effects, but also good wear resistance and durability, and also have special luminous properties, so that it can have a wide range of application prospects in cultural and tourism paving, commercial spaces, public places and residential areas.
[0003] Although traditional concrete or asphalt floors perform well in terms of structural stability and cost-effectiveness, they have certain limitations in terms of aesthetics and functionality. For example, ordinary concrete floors are single-colored, rough in appearance, and prone to cracks and wear after long-term use, affecting their appearance and service life. In addition, traditional floors lack sufficient brightness at night or in low-light environments, limiting their application in certain specific occasions. To overcome these limitations, researchers have been exploring new floor materials and technologies.
[0004] Chinese patent CN 114836065 B discloses a water-based inorganic antifungal ceramic topcoat and its preparation method and application. The ceramic topcoat comprises the following components by weight: 5-10 parts of fungicide, 0.1-0.5 parts of herbicide, 30-60 parts of inorganic resin, 20-40 parts of filler, 10-30 parts of silica sol and 0.1-0.8 parts of additive. This invention solves the technical problems of gloss loss, powdering and mold growth of topcoat caused by the metabolism of microorganisms on the surface of wet organic coatings and the aging of the organic coatings themselves, and achieves the technical effect of significantly inhibiting the growth of bacteria, microorganisms and plants on the surface of the coating. However, fillers are one of the main raw materials for improving the performance of ceramic topcoats. In this invention, fillers are directly mixed with inorganic resins and silica sols, and are prone to agglomeration after being placed for a long time, which affects the wear resistance and crack resistance of the coating.
[0005] Therefore, there is an urgent need for a luminous brightening floor containing an inorganic polymer silicone resin to have good wear resistance and crack resistance. Summary of the invention
[0006] In view of the existing technical problems, the purpose of the present invention is to provide a luminous brightening floor containing inorganic polymer silicone resin. The floor of the present invention has good wear resistance, good anti-fouling effect, good crack resistance, can reduce walking noise, reduce the heat island effect, and has the characteristics of luminous brightening effect and good decorative effect, and has a wide range of application scenarios.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] The present invention provides a luminous brightening floor containing inorganic polymer silicone resin, wherein the floor comprises from bottom to top: a plain soil ramming layer, a colored concrete layer, a colored aggregate polymer surface layer, a graphic acid coloring layer, and an elastic resin protective layer; wherein:
[0009] The elastic resin protective layer comprises the following raw materials by weight: 35-50 parts of inorganic resin, 15-25 parts of modified carbon nanotubes, 2-5 parts of hollow microspheres, 0.4-0.8 parts of dispersant, and 40-60 parts of water.
[0010] In some embodiments, a plurality of light guide tubes are laterally inserted through the rammed earth layer, and light guide fibers or LED light strips are inserted through the light guide tubes.
[0011] The reaction mechanism and effects of the present invention are as follows:
[0012] 1. Carbon nanotubes have a unique structure and excellent physical and chemical properties, which can significantly improve the performance of the coating, making the coating have excellent adhesion, wear resistance, corrosion resistance and anti-fouling properties. However, the properties of carbon nanotubes themselves lead to poor dispersion, affecting performance.
[0013] The present invention not only helps to improve the dispersibility of carbon nanotubes by inserting intermediates into the acidified carbon nanotubes, but also enhances their stability; then, by introducing hydrophilic ionic liquids through dispersion, grinding and ultrasonic treatment, the dispersibility of the modified carbon nanotubes in water can be further improved to form a more uniform and stable filler network structure. At the same time, when the ionic liquid covers the carbon nanotubes, the inorganic resin can move and unfold more flexibly on the surface of the carbon nanotubes when stretched by external forces, avoiding stress concentration, thereby reducing the risk of cracking of the material and improving the crack resistance of the material. In addition, the modified carbon nanotubes contain carbon-carbon double bonds, which may help to improve the compatibility with the dispersant, further avoid agglomeration, and improve the overall performance.
[0014] 2. Compared with polyamide fiber, poly fiber and viscose fiber, polypropylene fiber is light but strong. At the same time, polypropylene fiber has excellent electrical insulation and warmth retention, which can effectively improve the crack resistance of road base materials. However, the stability of polypropylene fiber under light and heat conditions is not satisfactory.
[0015] On the one hand, the present invention first uses benzophenone and N-vinyl acetamide to modify polypropylene fibers, and the modified primary polypropylene fibers can effectively improve stability. The applicant further grafts fumaric acid on the primary polypropylene fibers to effectively improve the dispersibility of the secondary polypropylene fibers in the matrix, thereby improving the interface bonding strength between the acrylic resin and the polypropylene fibers.
[0016] On the other hand, the present invention adds the prepared product 1 and product 2 for further modification to obtain modified polypropylene fiber. Nano-silicon dioxide and nano-calcium carbonate cannot be dispersed evenly when directly blended with raw materials. After agglomeration, weak areas will be generated in the system, affecting the compactness of the colored aggregate polymer surface layer. The present invention firstly utilizes sodium acrylate to modify nano-silicon dioxide, which is grafted onto secondary polypropylene fibers to help improve the dispersibility of the modified polypropylene fibers; at the same time, the nano-silicon dioxide particles make the surface of the modified polypropylene fibers uneven, thereby enhancing the bonding force between the modified polypropylene fibers and the raw materials, improving the material's crack resistance, and the nano-silicon dioxide particles can block part of the pores of the road base material, reducing water evaporation, thereby reducing the possibility of volume shrinkage and cracking of the colored aggregate polymer surface layer. The second is to modify nano calcium carbonate with 1-(3-aminopropyl) imidazole and KH560. After grafting to secondary polypropylene fibers, it helps to make the surface of polypropylene fibers easy to infiltrate, and further promotes the dispersion of modified polypropylene fibers; at the same time, nano calcium carbonate can not only fill the defects and weaknesses on the surface of secondary polypropylene fibers and improve the overall strength of the fibers, but also increase the surface roughness of secondary polypropylene fibers, thereby improving the mechanical properties of concrete; in addition, the five-membered ring in the imidazole group has a conjugated system, which can absorb ultraviolet light and improve the light stability and thermal stability of polypropylene fiber materials.
[0017] In some embodiments, the inorganic resin is sodium silicate resin and / or potassium silicate resin.
[0018] In some embodiments, the method for preparing the modified carbon nanotubes comprises the following steps:
[0019] A1. Mix carbon nanotubes and 50wt%-65wt% aqueous nitric acid solution, heat to 75-85°C, stir and react for 5-6h, cool, filter, wash and dry to obtain acidified carbon nanotubes;
[0020] A2. 3,5-dichlorobenzyl alcohol, sodium bicarbonate and dimethyl sulfoxide were mixed, stirred, introduced with inert gas, and a mixture of 1-(4-fluorophenyl)-3-butene-1-amine and dimethyl sulfoxide was added, heated to 45-55°C, distilled under reduced pressure, washed and dried to obtain an intermediate;
[0021] A3. The acidified carbon nanotubes obtained in step A1 and the intermediate obtained in step A2 are mixed, stirred, sulfuric acid is added, heated to 110-135°C, stirred for reaction for 2.5-3.5h, cooled, filtered, washed, and dried to obtain a powder;
[0022] A4. Disperse the powder obtained in step A3 into deionized water, stir, grind, add ionic liquid, stir, ultrasonically disperse, and dry to obtain modified carbon nanotubes.
[0023] In some embodiments, the ratio of the carbon nanotubes to the aqueous nitric acid solution in step A1 is 1 g: (40-60) ml.
[0024] In some embodiments, the molar ratio of 3,5-dichlorobenzyl alcohol to 1-(4-fluorophenyl)-3-butene-1-amine in step A2 is 1:(1.05-1.2).
[0025] In some embodiments, the mass ratio of the acidified carbon nanotubes to the intermediate in step A3 is 1:(2-3).
[0026] In some embodiments, the mass ratio of the powder to the ionic liquid in step A4 is 1:(1-1.6).
[0027] In some embodiments, the colored aggregate polymer surface layer comprises the following raw materials, measured by weight: 30-40 parts of colored gravel, 15-25 parts of glass stone, 7-13 parts of luminous stone, 25-35 parts of color enhancer, 3-7 parts of modified polypropylene fiber, 3-5 parts of acrylic resin, and 0.5-1.5 parts of pigment.
[0028] In some embodiments, the method for preparing the modified polypropylene fiber comprises the following steps:
[0029] S1. Mix nano-silica and water, heat to 70-80 ° C, stir to obtain a suspension, add sodium acrylate to the suspension while stirring, heat to 90-95 ° C, stir for 1-1.5h, filter, dry to obtain product 1, set aside;
[0030] S2. Mix nano calcium carbonate, KH560, 1-(3-aminopropyl) imidazole, isopropanol and water, heat to 40-50 ° C, stir to react, filter, wash, and dry to obtain product 2 for later use;
[0031] S3. Mix benzophenone and acetone, stir, add N-vinyl acetamide and water, sonicate to obtain a solution, drop the solution onto polypropylene fiber, perform photocatalytic reaction, wash, soak with dimethyl sulfoxide, soak at 50-60° C. for 10-15 hours, and dry to obtain primary polypropylene fiber;
[0032] S4. The primary polypropylene fiber obtained in step S3 is added to a xylene solution of dibenzoyl peroxide, an inert gas is introduced, fumaric acid is added, the reaction is stirred, filtered, washed, and dried to obtain a secondary polypropylene fiber;
[0033] S5. Disperse the product 1 obtained in step S1 and the product 2 obtained in step S2 into a 5wt%-10wt% sodium hydroxide aqueous solution, add the secondary polypropylene fiber obtained in step S4, introduce an inert gas, stir to react, filter, wash, and dry to obtain modified polypropylene fiber.
[0034] In some embodiments, the mass ratio of nano-silicon dioxide to sodium acrylate in step S1 is 1:(0.5-0.65).
[0035] In some embodiments, the mass ratio of nano-calcium carbonate, KH560 and 1-(3-aminopropyl)imidazole in step S2 is 1:(0.2-0.3):(0.3-0.4).
[0036] In some embodiments, the mass ratio of benzophenone, N-vinyl acetamide and polypropylene fiber in step S3 is (0.12-0.18):(0.06-0.12):1.
[0037] In some embodiments, the mass ratio of the primary polypropylene fiber to fumaric acid in step S4 is 1:(0.28-0.35).
[0038] In some embodiments, the mass ratio of the product 1, the product 2 and the secondary polypropylene fiber in step S5 is (0.2-0.3):(0.4-0.7):1.
[0039] In some embodiments, the raw material of the graphic acid coloring layer is a metal ion acid colorant.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] 1. The floor of the present invention has good wear resistance, good anti-fouling effect, good crack resistance, and has the characteristics of luminous brightening effect and good decorative effect. Its multi-layer structure can reduce walking noise and reduce the heat island effect, and its application scenarios are extremely diverse.
[0042] 2. The modified polypropylene fiber of the present invention can effectively improve stability, increase the dispersibility of polypropylene fiber, and improve the interfacial bonding force between acrylic resin and polypropylene fiber. In addition, the present invention further modifies the modified polypropylene fiber by adding the prepared product 1 and product 2, which helps to improve the dispersibility of the polypropylene fiber, and the product 1 and product 2 make the surface of the modified polypropylene fiber uneven, which improves the crack resistance of the material; at the same time, the five-membered ring of the imidazole group in product 2 has a conjugated system, which can absorb ultraviolet light and improve the light stability and thermal stability of the polypropylene fiber material.
[0043] 3. The modified carbon nanotubes of the present invention have good dispersibility and stability; at the same time, when the ionic liquid covers the carbon nanotubes, stress concentration can be avoided and the crack resistance of the material can be improved.
[0044] 4. The present invention uses infrared reflective pigments in the colored aggregate polymer surface layer, which can cool the ground by 4-5°C, thereby reducing the temperature of buildings and surrounding air, and helping to alleviate the urban heat island effect; in addition, the surface with a cooling effect will experience less thermal expansion and contraction, thereby extending the service life of the ground. DETAILED DESCRIPTION
[0045] The present invention will be described below in conjunction with specific embodiments. It should be noted that the following embodiments are examples of the present invention and are only used to illustrate the present invention, rather than to limit the present invention. Other combinations and various modifications within the concept of the present invention may be performed without departing from the spirit or scope of the present invention.
[0046] Each floor was prepared according to the ratio of each raw material and the preparation method specified in the following examples and comparative examples.
[0047] In order to facilitate those skilled in the art to implement the present invention, some raw material manufacturers of the embodiments and comparative examples are described as follows:
[0048] Polypropylene fiber: purchased from Taian Hongtong New Materials Co., Ltd.;
[0049] Acrylic resin: purchased from Shandong Lingsai Paint Co., Ltd.;
[0050] Sodium polyacrylate: purchased from Shandong Huiheng Biotechnology Co., Ltd.;
[0051] Color intensifier: purchased from Puli (Dongguan) New Materials Co., Ltd., Puli Zhongya color intensifier;
[0052] Pigment: Cobalt blue, purchased from Schett Pigment Company, USA;
[0053] Other raw materials are not specially specified and can be purchased from the market.
[0054] Preparation Example 1
[0055] The preparation method of modified polypropylene fiber A comprises the following steps:
[0056] S1. 600 g of nano-silica and 1000 g of water were mixed, heated to 75 ° C, stirred for 1 h to obtain a suspension, 360 g of sodium acrylate was added to the suspension while stirring, heated to 90 ° C, stirred for 1 h, filtered, and dried at 100 ° C to constant weight to obtain product 1, set aside;
[0057] S2. 600 g of nano-calcium carbonate, 150 g of KH560, 210 g of 1-(3-aminopropyl) imidazole, 400 ml of isopropanol and 1000 g of water were mixed, heated to 45 ° C, stirred for 1 h, filtered, washed three times with deionized water, and dried at 80 ° C to constant weight to obtain product 2 for later use;
[0058] S3. 30 g of benzophenone and 250 g of acetone were mixed and stirred for 30 min, 18 g of N-vinyl acetamide and 35 g of water were added, and ultrasonic treatment was performed for 30 min to obtain a solution, which was dropped onto 200 g of polypropylene fiber, and photocatalytic reaction was performed under ultraviolet light for 20 min, and then washed with water, anhydrous ethanol, and acetone once each, and then immersed in dimethyl sulfoxide, soaked at 55 ° C for 12 h, and dried at 60 ° C to constant weight to obtain primary polypropylene fiber;
[0059] S4. 100 g of the primary polypropylene fiber obtained in step S3 was added to 140 g of a 5 wt% xylene solution of dibenzoyl peroxide, nitrogen was introduced, 30 g of fumaric acid was added, the mixture was heated to 85 ° C and stirred for 1.5 h, filtered, washed three times with anhydrous ethanol, and dried at 95 ° C to constant weight to obtain a secondary polypropylene fiber;
[0060] S5. Disperse 20 g of product 1 obtained in step S1 and 44 g of product 2 obtained in step S2 into 8 wt % sodium hydroxide aqueous solution, add 80 g of secondary polypropylene fiber obtained in step S4, introduce nitrogen, heat to 60° C., stir to react for 18 h, filter, wash with water 3 times, and dry at 75° C. to constant weight to obtain modified polypropylene fiber A.
[0061] Preparation Example 2
[0062] The preparation method of modified polypropylene fiber B is the same as that of Preparation Example 1, except that the amount of fumaric acid added in step S4 is 25 g.
[0063] Preparation Example 3
[0064] The preparation method of modified polypropylene fiber C is the same as that of Preparation Example 1, except that the amount of product 2 added in step S5 is 30.4 g.
[0065] Preparation Example 4
[0066] The preparation method of modified polypropylene fiber D is the same as that of Preparation Example 1, except that the amount of product 1 added in step S5 is 14.4 g.
[0067] Preparation Example 5
[0068] The preparation method of modified carbon nanotube A comprises the following steps:
[0069] A1. 5 g of carbon nanotubes and 250 ml of a 60 wt % aqueous solution of nitric acid were mixed, heated to 80 ° C, stirred for 6 h, cooled to room temperature, filtered, washed with deionized water until neutral, and dried at 110 ° C for 12 h to obtain acidified carbon nanotubes;
[0070] A2. 17.7 g 3,5-dichlorobenzyl alcohol, 16 g sodium bicarbonate and 350 ml dimethyl sulfoxide were mixed, stirred for 20 min, nitrogen was introduced, 18.2 g 1-(4-fluorophenyl)-3-butene-1-amine and 150 ml dimethyl sulfoxide were added, heated to 50 ° C, distilled under reduced pressure, washed with deionized water 3 times, and dried at 110 ° C for 8 h to obtain an intermediate;
[0071] A3. 3 g of the acidified carbon nanotubes obtained in step A1 and 7.5 g of the intermediate obtained in step A2 were mixed, stirred for 30 min, 2 ml of a 50 wt% aqueous solution of concentrated sulfuric acid was added, heated to 125 ° C, stirred for 3 h, cooled to room temperature, filtered, washed with deionized water until neutral, and dried at 110 ° C for 8 h to obtain a powder;
[0072] A4. Disperse 2 g of powder obtained in step A3 into 100 ml of deionized water, stir for 10 min, grind for 2 h, add 2.3 g of 1-ethyl-3-methylimidazolium bromide, stir for 20 min, ultrasonically disperse for 2 h, and dry at 110 ° C for 12 h to obtain modified carbon nanotubes A.
[0073] Preparation Example 6
[0074] The preparation method of modified carbon nanotubes B is the same as that of Preparation Example 5, except that the amount of the intermediate added in step A3 is 5.4 g.
[0075] Preparation Example 7
[0076] The preparation method of modified carbon nanotube C is the same as that of Preparation Example 5, except that the amount of 1-ethyl-3-methylimidazolium bromide added in step A4 is 1.6 g.
[0077] Example 1
[0078] A luminous brightening floor containing inorganic polymer silicone resin, the floor comprises from bottom to top: a plain soil ramming layer, a colored concrete layer, a colored aggregate polymer surface layer, a graphic acid coloring layer, and an elastic resin protective layer; wherein,
[0079] In parts by weight, the elastic resin protective layer comprises the following raw materials: 42.5 parts of sodium silicate resin, 20 parts of modified carbon nanotubes A, 3.5 parts of hollow microspheres, 0.6 parts of sodium polyacrylate, and 50 parts of water; the colored aggregate polymer surface layer comprises the following raw materials: 35 parts of colored gravel, 20 parts of glass stone, 15 parts of luminous stone, 30 parts of color enhancer, 5 parts of modified polypropylene fiber A, 4 parts of acrylic resin, and 1 part of cobalt blue.
[0080] Example 2
[0081] A luminous brightening floor containing inorganic polymer silicone resin, the floor comprising from bottom to top: a plain soil ramming layer, a colored concrete layer, a colored aggregate polymer surface layer, a graphic acid coloring layer, and an elastic resin protective layer;
[0082] In parts by weight, the elastic resin protective layer comprises the following raw materials: 35 parts of sodium silicate resin, 15 parts of modified carbon nanotubes A, 2 parts of hollow microspheres, 0.4 parts of sodium polyacrylate, and 40 parts of water; the colored aggregate polymer surface layer comprises the following raw materials: 30 parts of colored gravel, 15 parts of glass stone, 7 parts of luminous stone, 25 parts of color enhancer, 3 parts of modified polypropylene fiber A, 3 parts of acrylic resin, and 0.5 parts of cobalt blue.
[0083] Example 3
[0084] A luminous brightening floor containing inorganic polymer silicone resin, the floor comprises from bottom to top: a plain soil ramming layer, a colored concrete layer, a colored aggregate polymer surface layer, a graphic acid coloring layer, and an elastic resin protective layer; wherein,
[0085] In parts by weight, the elastic resin protective layer comprises the following raw materials: 50 parts of sodium silicate resin, 25 parts of modified carbon nanotubes A, 5 parts of hollow microspheres, 0.8 parts of sodium polyacrylate, and 60 parts of water; the colored aggregate polymer surface layer comprises the following raw materials: 40 parts of colored gravel, 25 parts of glass stone, 13 parts of luminous stone, 35 parts of color enhancer, 7 parts of modified polypropylene fiber A, 5 parts of acrylic resin, and 1.5 parts of cobalt blue.
[0086] Example 4
[0087] A luminous brightening floor containing inorganic polymer silicone resin, the specific implementation method is the same as that of Example 1, except that the modified carbon nanotubes A are replaced by an equal amount of modified carbon nanotubes B.
[0088] Example 5
[0089] A luminous brightening floor containing inorganic polymer silicone resin, the specific implementation method is the same as that of Example 1, except that the modified carbon nanotubes A are replaced by an equal amount of modified carbon nanotubes C.
[0090] Example 6
[0091] A luminous brightening floor containing inorganic polymer silicone resin, the specific implementation method is the same as that of Example 1, except that an equal amount of modified polypropylene fiber B is used to replace modified polypropylene fiber A.
[0092] Example 7
[0093] A luminous brightening floor containing inorganic polymer silicone resin, the specific implementation method is the same as that of Example 1, except that an equal amount of modified polypropylene fiber C is used to replace the modified polypropylene fiber A.
[0094] Example 8
[0095] A luminous brightening floor containing inorganic polymer silicone resin, the specific implementation method is the same as that of Example 1, except that an equal amount of modified polypropylene fiber D is used to replace the modified polypropylene fiber A.
[0096] Comparative Example 1
[0097] A luminous brightening floor containing inorganic polymer silicone resin, the specific implementation method is the same as that of Example 1, except that an equal amount of commercially available carbon nanotubes is used to replace the modified carbon nanotube A.
[0098] Comparative Example 2
[0099] A luminous brightening floor containing inorganic polymer silicone resin, the specific implementation method is the same as that of Example 1, except that an equal amount of commercially available polypropylene fiber is used to replace the modified polypropylene fiber A.
[0100] Effect evaluation:
[0101] The floors prepared in the above-mentioned Examples 1-8 and Comparative Examples 1-2 were tested and analyzed, and the specific results are shown in Table 1.
[0102] The preparation method of the floor is as follows: the rammed earth layer is constructed according to the national standard, and a number of light guides are inserted horizontally, and light guide fibers or LED light strips are inserted in the light guides; the colored concrete layer is spread on the rammed earth layer with C40 fine stone colored concrete, with a thickness of 10cm; the colored aggregate polymer surface layer is mixed and stirred evenly according to the ratio of each raw material and then spread on the colored concrete layer, with a thickness of 1cm and the overall flatness and smoothness. It is strictly forbidden to cover the surface of the circular light guide rod to affect the light transmittance. After the colored aggregate polymer surface layer is made, the ground is first polished with a 500-mesh resin grinding disc, and then citric acid and oxalic acid are mixed in a volume ratio of 1:1 and sprayed on the polished ground, and then the copper brush plate installed with a stone renovation machine is used to brush the corroded surface, and after rinsing with clean water, it is finally cleaned with alkaline detergent and detergent. After drying, the next process can be constructed; the graphic acid coloring layer is sprayed or hand-painted on the surface of the colored aggregate polymer surface layer with metal ion acid colorant (metal ion acid colorant is Stone Tone Concrete Stain (concrete acid colorant); the elastic resin protective layer is mixed and stirred evenly according to the proportion of each raw material, and then evenly applied on the surface of the colored aggregate polymer surface layer and the graphic acid coloring layer by spraying or rolling, with a thickness of 0.5cm.
[0103] Performance Test:
[0104] (1) Abrasion resistance: Test the abrasion resistance in accordance with GB / T 23988-2009 “Determination of abrasion resistance of coatings by falling sand method”;
[0105] (2) Cracking resistance: The cracking resistance is measured with reference to GB / T 50082-2009 "Standard for test methods for long-term properties and durability of ordinary concrete".
[0106] Table 1
[0107] Serial number Wear resistance (L / μm) <![CDATA[Total crack area (mm 2 )]]> Example 1 2.8 38.1 Example 2 3.1 40.4 Example 3 3.0 39.7 Example 4 5.4 50.4 Example 5 4.9 62.3 Example 6 2.8 57.6 Example 7 2.9 64.8 Example 8 2.9 69.6 Comparative Example 1 6.8 74.5 Comparative Example 2 2.9 76.7
[0108] From the results in Table 1, it can be seen that the floor prepared in Examples 1-3 has good wear resistance and crack resistance, and has good market value.
[0109] Examples 4-5 and Comparative Example 1, compared with Example 1, when preparing modified carbon nanotubes, Example 4 changes the mass ratio of acidified carbon nanotubes and intermediates, and the stability is weakened; Example 5 changes the mass ratio of powder and ionic liquid, and the hydrophilicity is weakened, which will affect the wear resistance and crack resistance of the floor; and Comparative Example 1 uses an equal amount of commercially available carbon nanotubes to replace modified carbon nanotube A, which greatly reduces the wear resistance and crack resistance of the floor.
[0110] In Examples 6-8 and Comparative Example 2, compared with Example 1, when preparing modified polypropylene fibers, Example 6 changes the mass ratio of primary polypropylene fibers and fumaric acid, resulting in decreased dispersibility; Examples 7-8 change the mass ratio of product 1, product 2, and secondary polypropylene fibers, resulting in decreased density and decreased roughness, which will affect the crack resistance of the floor; while Comparative Example 2 uses an equal amount of commercially available polypropylene fibers to replace modified polypropylene fibers A, resulting in a significant decrease in the crack resistance of the floor. In addition, since the modified polypropylene fibers are the raw materials for the colored aggregate polymer surface layer, they have little effect on the wear resistance of the floor surface layer.
[0111] The above is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present application. Although the present application is disclosed as above in the preferred embodiment, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution.
Claims
1. A luminous brightening floor containing inorganic polymer silicone resin, characterized in that: The floor comprises, from bottom to top, a rammed earth layer, a colored concrete layer, a colored aggregate polymer surface layer, a graphic acid coloring layer, and an elastic resin protective layer; wherein, The elastic resin protective layer comprises the following raw materials by weight: 35-50 parts of inorganic resin, 15-25 parts of modified carbon nanotubes, 2-5 parts of hollow microspheres, 0.4-0.8 parts of dispersant, and 40-60 parts of water.
2. The luminous brightening floor containing inorganic polymer silicone resin according to claim 1, characterized in that: The inorganic resin is sodium silicate resin and / or potassium silicate resin.
3. The luminous brightening floor containing inorganic polymer silicone resin according to claim 1, characterized in that: The method for preparing the modified carbon nanotubes comprises the following steps: A1. Mix carbon nanotubes and 50wt%-65wt% aqueous nitric acid solution, heat to 75-85°C, stir and react for 5-6h, cool, filter, wash and dry to obtain acidified carbon nanotubes; A2. 3,5-dichlorobenzyl alcohol, sodium bicarbonate and dimethyl sulfoxide were mixed, stirred, introduced with inert gas, and a mixture of 1-(4-fluorophenyl)-3-butene-1-amine and dimethyl sulfoxide was added, heated to 45-55°C, distilled under reduced pressure, washed and dried to obtain an intermediate; A3. The acidified carbon nanotubes obtained in step A1 and the intermediate obtained in step A2 are mixed, stirred, sulfuric acid is added, heated to 110-135°C, stirred for reaction for 2.5-3.5h, cooled, filtered, washed, and dried to obtain a powder; A4. Disperse the powder obtained in step A3 into deionized water, stir, grind, add ionic liquid, stir, ultrasonically disperse, and dry to obtain modified carbon nanotubes.
4. The luminous brightening floor containing inorganic polymer silicone resin according to claim 3, characterized in that: The mass ratio of the acidified carbon nanotubes to the intermediate in step A3 is 1:(2-3).
5. The luminous brightening floor containing inorganic polymer silicone resin according to claim 3, characterized in that: The mass ratio of the powder to the ionic liquid in step A4 is 1:(1-1.6).
6. The luminous brightening floor containing inorganic polymer silicone resin according to claim 1, characterized in that: The colored aggregate polymer surface layer comprises the following raw materials by weight: 30-40 parts of colored gravel, 15-25 parts of glass stone, 7-13 parts of luminous stone, 25-35 parts of color enhancer, 3-7 parts of modified polypropylene fiber, 3-5 parts of acrylic resin, and 0.5-1.5 parts of pigment.
7. The luminous brightening floor containing inorganic polymer silicone resin according to claim 6, characterized in that: The preparation method of the modified polypropylene fiber comprises the following steps: S1. Mix nano-silica and water, heat to 70-80 ° C, stir to obtain a suspension, add sodium acrylate to the suspension while stirring, heat to 90-95 ° C, stir for 1-1.5h, filter, dry to obtain product 1, set aside; S2. Mix nano calcium carbonate, KH560, 1-(3-aminopropyl) imidazole, isopropanol and water, heat to 40-50 ° C, stir to react, filter, wash, and dry to obtain product 2 for later use; S3. Mix benzophenone and acetone, stir, add N-vinyl acetamide and water, sonicate to obtain a solution, drop the solution onto polypropylene fiber, perform photocatalytic reaction, wash, soak with dimethyl sulfoxide, soak at 50-60° C. for 10-15 hours, and dry to obtain primary polypropylene fiber; S4. The primary polypropylene fiber obtained in step S3 is added to a xylene solution of dibenzoyl peroxide, an inert gas is introduced, fumaric acid is added, the reaction is stirred, filtered, washed, and dried to obtain a secondary polypropylene fiber; S5. Disperse the product 1 obtained in step S1 and the product 2 obtained in step S2 into a 5wt%-10wt% sodium hydroxide aqueous solution, add the secondary polypropylene fiber obtained in step S4, introduce an inert gas, stir to react, filter, wash, and dry to obtain modified polypropylene fiber.
8. The luminous brightening floor containing inorganic polymer silicone resin according to claim 7, characterized in that: The mass ratio of the primary polypropylene fiber to fumaric acid in step S4 is 1:(0.28-0.35).
9. The luminous brightening floor containing inorganic polymer silicone resin according to claim 7, characterized in that: The mass ratio of the product 1, the product 2 and the secondary polypropylene fiber in step S5 is (0.2-0.3):(0.4-0.7):
1.
10. The luminous brightening floor containing inorganic polymer silicone resin according to claim 1, characterized in that: The raw material of the graphic acid coloring layer is a metal ion acid colorant.
Citation Information
Patent Citations
Water-based inorganic antifungal ceramic topcoat and preparation method and application thereof
CN114836065B